Aplikasi Ulangan Harian Dan Bank Soal SMP Kristen YBPK 1 Surabaya - Eldwin Surya Kusuma; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2017)
At this time, SMP Christian YBPK 1 Surabaya had adopted a National Exam Online System. But this time the SMP Christian YBPK 1 Surabaya doesnt have a softwareju to hold a practice test by using a computer. This causes students to feel confused when they working on the national exam online for the first time. Additionally at this time Christian SMP YBPK 1 Surabaya hold daily tests using paper, whenever the teacher held a test, it caused wasting time to create questions and check the work of their students. This application is built using HTML, PHP, JavaScript, and MySQL database. Display applications using Bootstrap template. Voice recording feature is built with francium-voice template. The results of the development of this application is this software is able to create a question, can make test based from database, Automatic checking on the answers to the multiple choice questions, assigning question value to the answers to essay, lab schedule, the data value of students per period. Users can also see informations about how many questions that have been used through the results of statistical reports.